Watermark Embedder and Image Authenticator (WEIA) - Lu, Chun Ling; Khor, Hui Liang; Liew, Siau-Chuin (DEStech Publications, 2014)
This research paper discusses the development of a watermark embedder and image authenticator (WEIA) to ensure the authenticity and integrity of medical images. WEIA is also able to send and receive medical images within a peer-to-peer network. Experiments also shows that WEIA successfully embeds chosen watermarking scheme and able to detect tampering and recovers tampered image.